An Analysis of the Effectiveness of the Legal Framework on Access to Justice by Children in Juvenile Detention in Uganda - Deborah Watum Ajok (Uganda Christian University, 2024)
This study analyses the effectiveness of the legal framework on access to justice by children in juvenile detention in Uganda. It offers a background into the system and practice of juvenile detention, showing its history and development both internationally and within Uganda. It looks at the legal regime governing juvenile detention and the wider system within which children are protected. The primary laws analyzed in Uganda include the Constitution, The Children’s Act as amended and all the related laws thereunder. It further looks at the international and regional instruments signed for the protection of children and for the treatment of prisoners both adult and juvenile. In order to determine the effectiveness of all the above in access to justice by children in detention, the socio-cultural framework of the country is analyzed and the gaps in the enforcement of the laws are mentioned. The challenges to the access of justice of children are seen to be both legal and social, and the solutions entail a repair on both sides. The research recommends that specific laws codifying the treatment of children in juvenile detention be the priority, and a mechanism of controlling the discretion which officers exercise in juvenile matters be developed.